Fluorescence in situ hybridization method using peptide nucleic acid probes for rapid detection of Lactobacillus and Gardnerella spp - Machado, António (2013)
Background: Bacterial vaginosis (BV) is a common vaginal infection occurring in women of reproductive age. It is widely accepted that the microbial switch from normal microflora to BV is characterized by a decrease in vaginal colonization by Lactobacillus species together with an increase of Gardnerella vaginalis and other anaerobes. Our goal was to develop and optimize a novel Peptide Nucleic Acid (PNA) Fluorescence in situ Hybridization assay (PNA FISH) for the detection of Lactobacillus spp. and G. vaginalis in mixed samples. Results: Therefore, we evaluated and validated two specific PNA probes by using 36 representative Lactobacillus strains, 22 representative G. vaginalis strains and 27 other taxonomically related or pathogenic bacterial strains commonly found in vaginal samples. The probes were also tested at different concentrations of G. vaginalis and Lactobacillus species in vitro, in the presence of a HeLa cell line. Specificity and sensitivity of the PNA probes were found to be 98.0% (95% confidence interval (CI), from 87.8 to 99.9%) and 100% (95% CI, from 88.0 to 100.0%), for Lactobacillus spp.; and 100% (95% CI, from 92.8 to 100%) and 100% (95% CI, from 81.5 to 100.0%) for G. vaginalis. Moreover, the probes were evaluated in mixed samples mimicking women with BV or normal vaginal microflora, demonstrating efficiency and applicability of our PNA FISH. Conclusions: This quick method accurately detects Lactobacillus spp. and G. vaginalis species in mixed samples, thus enabling efficient evaluation of the two bacterial groups, most frequently encountered in the vagina.